2011
DOI: 10.1007/s11103-011-9824-7
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation and nitration levels of photosynthetic proteins are conversely regulated by light stress

Abstract: Using a label-free mass spectrometric approach, we investigated light-induced changes in the distribution of phosphorylated and nitrated proteins within subpopulations of native photosynthetic complexes in the thylakoid membrane of Arabidopsis thaliana leaves adapted to growth light (GL) and subsequently exposed to high light (HL). Eight protein phosphorylation sites were identified in photosystem II (PSII) and the phosphorylation level of seven was regulated by HL as determined based on peak areas from ion ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 58 publications
(80 reference statements)
0
31
0
3
Order By: Relevance
“…Tyrosine nitration can change the function of the protein in several ways: function gain; no effect on function; and inhibition of function, the latter being the most common consequence of tyrosine nitration (Greenacre and Ischiropoulos, 2001; Radi, 2004). On the other hand, tyrosine nitration may influence many signal transduction pathways because this modification prevents phosphorylation of tyrosine and consequently affects one regulatory mechanism (Galetskiy et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Tyrosine nitration can change the function of the protein in several ways: function gain; no effect on function; and inhibition of function, the latter being the most common consequence of tyrosine nitration (Greenacre and Ischiropoulos, 2001; Radi, 2004). On the other hand, tyrosine nitration may influence many signal transduction pathways because this modification prevents phosphorylation of tyrosine and consequently affects one regulatory mechanism (Galetskiy et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Tyr nitration inhibits the activity of both FNR (Chaki et al, 2011) and chloroplast SUPEROXIDE DISMUTASE3, an important scavenger of superoxide anion (O 2 Moreover, the activities of GLYCERALDEHYDE-3-PHOSPHATE DEHYDROGENASE (GAPDH; LozanoJuste et al, 2011) and b-CARBONIC ANHYDRASE (CA), which are involved in photosynthetic carbon metabolism, were decreased upon Tyr nitration . It has been hypothesized that Tyr nitration may disturb the electron transfer chain, because (1) Tyr nitration of the Tyr-262 in the D1 protein may lead to the release of the secondary electron-accepting plastoquinone of PSII from the binding pocket and (2) the double Tyr nitration of PSI subunit D may disturb the flow of electrons from PSI to FERREDOXIN (Galetskiy et al, 2011b). It has also been shown that numerous proteins in PSII monomers, dimers, and PSII-LHCII supercomplexes possess low levels of phosphorylation and high levels of nitration under standard growth conditions, but under high-light conditions, the situation is reversed (Galetskiy et al, 2011b).…”
Section: Tyr Nitration and S-nitrosylationmentioning
confidence: 99%
“…It has been hypothesized that Tyr nitration may disturb the electron transfer chain, because (1) Tyr nitration of the Tyr-262 in the D1 protein may lead to the release of the secondary electron-accepting plastoquinone of PSII from the binding pocket and (2) the double Tyr nitration of PSI subunit D may disturb the flow of electrons from PSI to FERREDOXIN (Galetskiy et al, 2011b). It has also been shown that numerous proteins in PSII monomers, dimers, and PSII-LHCII supercomplexes possess low levels of phosphorylation and high levels of nitration under standard growth conditions, but under high-light conditions, the situation is reversed (Galetskiy et al, 2011b). Thus, the complex and conversely regulated nitration and phosphorylation events might control the stability, turnover, and reassembly of the PSII core complexes and the LHC antenna upon light stress (Galetskiy et al, 2011b).…”
Section: Tyr Nitration and S-nitrosylationmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors discussed the importance of these posttranslational modifications in the acclimation to high salinity. In contrast, nitration of specific tyrosine of Dl protein (PSBA) of photosystem II leads to the dissociation of the PS II dimers and PS II-LHCII supercomplexes during high light stress (Galetskiy et al 2011). Carbonic anhydrase in sunflower (Chaki et al 2013); and chloroplastic glycerinaldehyde-3-phosphate dehydrogenase in Arabidopsis (Lozano-Juste et al 2011) were also among the Tyr-nitrated proteins under stressS conditions that showed reduced activity.…”
Section: No-and Salt-induced Programmed Cell Deathmentioning
confidence: 99%